PEMANFAATAN INFORMATION & COMMUNIACTION TECHNOLOGY(ICT) PADA PERUSAHAAN DAN INSTANSI PEMERINTAH DALAM RANGKA PENINGKATAN KUALITAS PUBLIC SERVICES - Wibowo Wibowo (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2008)
The government and the company are agents which provides services should improve the quality of delivering their services. For winning competition, a company should have strategies/methods how to make client or customers interested in services delivered. Government institution should improve quality of services, so citizens will appreciate to government institution and would contribute in development process. How did they do? Adopted and implemented information & technology communication is one of the answer. Based on experience in many countries and companies are the evidences of the usefulness of implementation of ICT